PENGEMBANGAN PROTOTIPE ALAT JAMUR CABANG OLAHRAGA SENAM ARTISTIK PUTRA DI PROVINSI JAWA TENGAH - Tommy Soenyoto (Universitas Negeri Semarang, 2014)
The purpose of the research was to develop a model of mushrooms apparatus for junior and senior male artistic gymnastics levels with the aim to improve motor skills on a pommel horse. This equipment can be used for practicing male artistic gymnastics on beginner level , junior and senior as well as to be used for competition. This study used a qualitative approach for model development. The data collected in this study either at initial as well as trial stages were qualitative data. The main procedure in the research and development consists of five steps, namely: (1) To analyze the apparatus to be developed ; (2) To develop the initial apparatus; (3) Validation by the expert; (4) The field trials; (5) Revision of the apparatus. The results of this study concluded that the development model of mushrooms apparatus for male artistic gymnastics can be used to (1) improve the skills of motion on the pommel horse for gymnastics on junior and senior levels; (2) As a means of training for male artistic gymnastics; (3) As a means of competition for male artistic gymnastics at beginner level.